Pathways to Endocrine Therapy Resistance in Breast Cancer - Haque, Md. Moquitul; Desai, Kartiki V. (Frontiers in Endocrinology, 2019)
Breast cancers with positive expression of Estrogen Receptor (ER+) are treated with anti-hormone/endocrine therapy which targets the activity of the receptor, the half-life of the receptor or the availability of estrogen. This has significantly decreased mortality in women with ER+ breast cancer, however, about 25-30% of treated women run the risk or recurrence due to either intrinsic or acquired resistance to endocrine therapies. While ER itself is a predictor of response to such therapies, there exists a need to find more biomarkers and novel targets to treat resistant tumors. In this review, we summarize the known mechanisms and describe the ability of genomics in unraveling rare mutations and gene rearrangements that may impact the development of resistance and therefore treatment of ER+ breast cancer in the near future.